Komunikasi Interpersonal; Peran Dakwah Dalam Membangun Narasi Islam Wasathiyah di Era Digital - AT. Muhammad Al Azmi (Raudhatun Najah Publisher, 2024)
The development of digital technology has transformed the way da'wah communication is conducted; however, interpersonal approaches continue to play a crucial role in shaping moderate religious understanding. Islam Wasathiyah, as a representation of balanced, tolerant, and inclusive Islam, requires communication strategies that are not only informative but also capable of addressing emotional and relational dimensions. This study aims to examine how interpersonal communication is utilized in da'wah activities to construct the narrative of Islam Wasathiyah amid the digital era, which is characterized by polarization and the widespread dissemination of extreme religious information. Employing a descriptive qualitative approach, data were collected through interviews with Islamic preachers (da'i), observers of da'wah media, and analyses of digital-based da'wah content. The findings reveal that interpersonal communication, whether conducted face-to-face or through digital platforms that facilitate two-way interaction, such as social media and discussion forums, possesses significant potential to foster emotional closeness, trust, and a deeper understanding of moderate Islamic values. This approach has proven more effective in countering rigid and intolerant religious narratives while simultaneously strengthening collective awareness of the importance of religious moderation. These findings highlight the necessity of enhancing interpersonal communication capacities within digital da'wah strategies to preserve social harmony and promote the universal Islamic values of rahmatan lil ‘alamin (mercy to all creation).